Optimization of Disperse Blue 3 mineralization by UV-LED/FeTiO3 activated persulfate using response surface methodology - Silveira, Jefferson E.; Claro, Elis Marina Turini [UNESP]; Paz, Wendel S.; Oliveira, Adriana S.; Zazo, Juan A.; Casas, Jose A. (Elsevier, 2018)
Response surface methodology based on Box-Behnken design (BBD) was successfully applied for the optimization of the UV-LED/FeTiO3 activated persulfate (PS) process. Disperse Blue 3 (DB3) azo dye oxidation was carried out in a quartz jacketed stirred batch reactor using 405 nm UV at 10 W/m−2 as radiation source. The effects of temperature, catalyst concentration and persulfate dose upon the total organic carbon (TOC) removal were investigated. Optimum operating conditions were found to be: ilmenite: 320 mg/L−1, PS: 1.56 g/L−1 and 67 °C. Under these conditions, 96% mineralization was achieved. Ecotoxicity of the final effluent was evaluated using Aliivibrio fischeri bacteria, finding a negligible toxicity.
Keywords: Box-Behnken design; FeTiO3; Optimization; Photo-reduction